Drug Nanocrystals for Active Tumor-Targeted Drug Delivery - Linwei Lu; Qianzhu Xu; Jun Wang; Sunyi Wu; Zimiao Luo; Weiyue Lu (MDPI AG, 2022)
Drug nanocrystals, which are comprised of active pharmaceutical ingredients and only a small amount of essential stabilizers, have the ability to improve the solubility, dissolution and bioavailability of poorly water-soluble drugs; in turn, drug nanocrystal technology can be utilized to develop novel formulations of chemotherapeutic drugs. Compared with passive targeting strategy, active tumor-targeted drug delivery, typically enabled by specific targeting ligands or molecules modified onto the surface of nanomedicines, circumvents the weak and heterogeneous enhanced permeability and retention (EPR) effect in human tumors and overcomes the disadvantages of nonspecific drug distribution, high administration dosage and undesired side effects, thereby contributing to improving the efficacy and safety of conventional nanomedicines for chemotherapy. Continuous efforts have been made in the development of active tumor-targeted drug nanocrystals delivery systems in recent years, most of which are encouraging and also enlightening for further investigation and clinical translation.